1-ethyl-3-methylimidazolium tetrafluoroborate (EMI-BF4) as an ionic liquid-type electrolyte additive to enhance the low-temperature performance of LiNi0.5Co0.2Mn0.3O2/graphite batteries. (10th September 2019) - Wang, Wenlian; Yang, Tianxiang; Li, Shuai; Fan, Weizhen; Zhao, Xiaoyang; Fan, Chaojun; Yu, Le; Zhou, Shaoyun; Zuo, Xiaoxi; Zeng, Ronghua; Nan, Junmin
Abstract: A 1-ethyl-3-methylimidazolium tetrafluoroborate (EMI–BF4 ) ionic liquid is introduced into an electrolyte as a functional additive to enhance the low-temperature performance of LiNi0.5 Co0.2 Mn0.3 O2 (NCM523)/graphite batteries. Linear sweep voltammetry (LSV), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) tests show that EMI–BF4 can be oxidized in advance and produce low impedance solid-electrolyte interphase (SEI) films on the electrode surfaces. Compared with the batteries without the EMI–BF4 additive, the capacity retention of the NCM523/graphite batteries with 1% EMI–BF4 additive is enhanced from 82.3% to 93.8% after 150 cycles at a low temperature of −10 °C. In addition, at −30 °C, the discharge capacity of the batteries with 1% EMI–BF4 additive is nearly doubled. And at the room temperature of 25 °C and after 400 cycles, the capacity retention also increases from 80.3% to 85.9%, and the coulomb efficiency remains at approximately 100%. These results demonstrate that EMI–BF4 used as a functional electrolyte additive has promising prospects for application to improve the low-temperature performance of NCM523-based lithium-ion batteries. Graphical abstract: Image 1069882 Highlights: 1-ethyl-3-methylimidazolium tetrafluoroborate (EMI-BF4 ) is evaluated as a low temperature electrolyte additive. EMI-BF4 can form interfacial films on both electrode surfaces of NCM523/graphite batteries. The interfacial films formed on both electrodes improve their cycle stability. The capacity retention rate of the batteries with EMI-BF4 is increased under low temperature.